Sistema embarcado para estimação de torque, velocidade e eficiência em motores de indução - Adissi, Marcéu Oliveira (2012)
The presented work aims at monitoring in real time the important parameters in induction motors in a non-invasive manner. A method for estimation of torque, shaft speed and energy efficiency has been developed. An embedded system is employed for acquiring electrical signals from the motor and local processing. The calculated values are transmitted to a monitoring unit through an IEEE 802.15.4-based wireless sensor network. At the base unit, various motors can be monitored in real time. To choose the method to be used, a survey on the main methods was made. The method by air-gap torque was considered the most appropriate to the requirements for being accurate and non-invasive. An experimental study was conducted to observe the accuracy of the estimated methods used, and the relationship between the wireless sensor network performance and the spectral occupancy at the operating environment. Therefore, the embedded system was deployed on a workbench of dynamic sinusoidal torque in an industrial environment. The performance of the embedded system and the estimation results were extremely positive. The results show that even with the difficulties of wireless transmission in some scenarios, the system was fully capable of providing processed information for the monitoring.